THE INFLUENCE OF RELIGIONS ON THE CONSTRUCTION OF CULTURAL IDENTITY: IN DIFFERENT RELIGIOUS TRADITIONS IN SOCIETY - Bento, Lisandra Taschetto Murini; Murini, Cléber Taschetto; Bento, Cleber Junior Pereira (Seven Editora, 2025)
Religion is presented as a fundamental element in the construction of behaviors, social norms and values, shaping the academic trajectory and social interactions of students. The article explores the influence of religion on the cultural identity and educational experience of students taking professional education courses in the QualificarES Program. It highlights the importance of understanding religious diversity in the educational context, promoting a more inclusive and respectful environment. Qualitative research, based on content analysis, reveals that religiosity can be a motivational factor, but it also presents challenges in contexts of diversity. The conclusion emphasizes the need for a careful look at cultural differences and the importance of educational policies that respect religious plurality, promoting intercultural dialogue and harmonious coexistence among students. The study seeks to contribute to a more humanized and equitable education, recognizing the relevance of religious diversity in the training of students.DOI: https://doi.org/10.56238/sevened2025.029-118